Assessing authentic tasks: alternatives to mark-schemes - Wiliam, Dylan (NOMAD Nordic Studies in Mathematics Education, 1994)
The kinds of authentic tasks that have been used in national assessments in Eng- land and Wales over the last thirty years - typically open-ended, ’pure’ investigative tasks - are described, and the marking schemes used for their assessment are classified as either task-specific or generic. Generic schemes are further classified according to whether the ’degree of difficulty’ of the task or the ’extent of progress’ through the task is given most emphasis. A view of validation is presented that requires consideration of the value implications and social consequences of imple- menting assessment procedures, and it is argued that both task-specific and generic schemes will have the effect of stereotyping student approaches to these tasks. An alternative paradigm to norm-referenced and criterion-referenced interpretations of assessments, entitled ’construct-referenced’ assessment, is proposed as being more consistent with the rationale behind such authentic assessments. Suggestions for the implementation of such a system are made and indices derived from signal- detection theory are suggested as appropriate measures for the evaluation of the accuracy of such assessments.